PEMIKIRAN ISLAM TENTANG KEADILAN DAN PENGAWASAN PEMILU: MENGUATKAN KESADARAN POLITIK PEMILIH PEMULA - Hasan Ansori, Ari; Herlina, Lina (Staisman Press, 2024)
Abstract This study aims to examine the influence of understanding justice in Islam on the political awareness of first-time voters in Indonesia, particularly in the context of the 2024 Regional Head Elections. It also explores how electoral supervision can enhance political participation among first-time voters. The main issue addressed in this research is the low political awareness among first-time voters, which stems from a lack of knowledge and understanding regarding their political rights and responsibilities within the democratic process. Additionally, the weakness of electoral supervision, particularly the insufficient or nonexistent involvement of first-time voters, exacerbates this situation. The principles of justice in Islam, which emphasize transparency, accountability, and social responsibility, are considered a potential solution for improving the political awareness of first-time voters. This research employs a quantitative method using survey techniques, involving 300 respondents aged 17 to 25 years, selected through purposive sampling. The collected data were analyzed using simple statistical methods to test the relationships between the understanding of justice in Islam, the effectiveness of electoral supervision, and the political awareness of first-time voters. The findings indicate that a deeper understanding of the principles of justice in Islam significantly contributes to enhancing political awareness and the active participation of first-time voters in the electoral supervision process. This study is expected to provide practical contributions to the design of political education programs based on Islamic justice values, as well as strengthen the role of first-time voters in improving the quality of democracy in Indonesia. Keywords: justice, electoral supervision, political awareness, first-time voters, political education.